Relationships Between Religiosity, Self-Esteem, and Purpose in Life - Carmen María Salvador-Ferrer (Spirituality Studies)
This exploratory study analyzes whether self-esteem and religiosity influence life purpose. A questionnaire was used in which there are three scales: Purpose of Life (García-Alandete, Martínez and Nohales 2013; PIL-10 with Cronbach’s alpha score=.904); The Religiosity Scale (Koenig, Parkerson and Meador 1997; Duke Religion Index with Cronbach’s alpha score=.890); and Self-Esteem Scale (Rosenberg 1965; Rosenberg Self-Esteem Scale with Cronbach’s alpha score=.875). This instrument was administered to 963 participants of which 35% were women and 65% were men. The correlation data shows statistically significant relationships between most variables, except the association between negative self-esteem vs. religiosity. In regression analysis, the findings indicate that the three variables (religiosity, positive self-esteem, and negative self-esteem) have a statistically significant influence on the purpose of life. We found the highest positive self-esteem, followed by religiosity and, in the opposite extreme, with a negative impact, negative self-esteem. With mediation analysis, it is found that the relationship between religiosity and purpose of life is mediated by negative self-esteem. Religiosity can play a relevant role in self-esteem and purpose in life. These data indicate that if religious practices are worked, people will show a better value of themselves and will mark their purpose in life more clearly.